2017
DOI: 10.3389/fpls.2017.00464
|View full text |Cite
|
Sign up to set email alerts
|

1-Aminocyclopropane-1-Carboxylate Oxidase Induction in Tomato Flower Pedicel Phloem and Abscission Related Processes Are Differentially Sensitive to Ethylene

Abstract: Ethylene has impact on several physiological plant processes, including abscission, during which plants shed both their vegetative and reproductive organs. Cell separation and programmed cell death are involved in abscission, and these have also been correlated with ethylene action. However, the detailed spatiotemporal pattern of the molecular events during abscission remains unknown. We examined the expression of two tomato ACO genes, LeACO1, and LeACO4 that encode the last enzyme in ethylene biosynthesis, 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…The analysis also revealed that the ACO1 protein is localised to the same area (Chersicola et al . 2017). In that study, ACO1 was found mainly in the phloem companion cells, which was thus suggested as the side for synthesis of ethylene.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis also revealed that the ACO1 protein is localised to the same area (Chersicola et al . 2017). In that study, ACO1 was found mainly in the phloem companion cells, which was thus suggested as the side for synthesis of ethylene.…”
Section: Discussionmentioning
confidence: 99%
“…(2017). Parapalast Plus‐embedded tissue sections were placed on Superfrost Ultra Plus slides (Menzel‐Gläser).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations